(untitled) (Revista Ciência Agronômica, 2023)
The 2,4-D herbicide is widely used in Brazilian and global agriculture to control weeds. It is potentially toxic to mankind, and one of the herbicides final destinations is the soil. The aim of the study was to determine the spatial correlation of 2,4-D herbicide in soil attributes after 12 months of application. The experiment was conducted in an agricultural area of 5.04 ha in the municipality of Nova Santa Rosa/PR, in 2011 and 2012. Two soil samples collections were performed: collection 1 (09/03/2011) and collection 2 (08/25/2012), both of which were made 12 months after 2,4-D application. The herbicide was applied in a single dose of 1.5 L ha-1 in 09/2010 and in two doses in 09/2011 (1.0 L ha-1or 1.5 L ha-1 2,4-D). The correlation between soil attributes and 2,4-D was determined with the use of a spatial correlation matrix. The 2,4-D soil residues varied widely from one location to another in the same area, with points of no detection of the active ingredient. It was not possible to detect differences between 1.0 L ha-1 and 1.5 L ha-1 2,4-D treatments. Several factors may have interfered in the herbicide residues in the soil, including: climate, product characteristics, physical and chemical soil characteristics, soil management, among others. The spatial correlation of the soil attributes and 2,4-D residues in the soil proved to be an important tool to verify one parameter interference over another.